ADVOKASI KEBIJAKAN LEMBAGA PENYIARAN PUBLIK LOKAL UNTUK REVISI UU PENYIARAN DI INDONESIA: Indonesia - Masduki; Anshori, Adam (UII, 2024)
This paper explores community service activities to strengthen the political and structural position of the Local Public Broadcasting Institution (LPPL), the key pillar of broadcast democratization in Indonesia. This community service is in partnership with two non-profit institutions called Rumah Perubahan LPP and PERSADA.ID, which are managed by media activists and professionals from various organizations. The key program is drafting and publishing position paper as an effort to strengthen the position of local public radio within the upcoming Broadcast Law no. 32/2002 revision. It takes in the form of a webinar and workshop on producing position paper to post to the new Broadcasting Law, which based on the LPPL's ​​broadcasters’ aspirations, both in English and Indonesia. This program involves LPPL activists as the workshop organizers, participants and resource persons, and can be a model for future community service in broadcasting advocacy. The program results a publicly accessible document of ​​policy paper about various issues of local broadcasting in Indonesia (English and Indonesia) and recommendation of collaboration among universities and public broadcasters to advocate the policy.